Our home and our cities - present and future investigation in the aim of people’s health - Remoaldo, Paula Cristina (Horizonte Sanitario, 2017)
Nowadays, the “Horizonte Sanitario’s” journal is a relevant Journal in health rules, mainly to Latin American countries, which involves a huge territory. Some of those countries are achieving the last phase of what it’s been called Theoretical and Epidemiological Transition. The invoked theoretical framework had as its mentor Abdel Omran, in 1971. It highlights the type/spectrum of diseases that each country and region has in connection to the type of achieved development. It is highly connected within the Theory of Demographic Transition (focused in the evolution of the fecundity and mortality rates) proposed by Thompson, in 1929. In this case, starting from the observation of European countries.